Influence of the Capped Polymer on the Optical of ZnS:Cu Nanocrystalline Thin Films - Thi, Tran Minh; Vuong, Nguyen Minh (Communications in Physics, 2012)
The ZnS:Cu nanopowders were synthesized by the wet chemical method with Cu concentrations of 0.1, 0.15, 0.2, 0.3 and 0.4%. The microstructure of samples was investigated by the X-ray diffraction (XRD) measurement. The results show that the prepared samples belong to the Wurtzite structure with the average particle size of about 3–7 nm. The highest luminescence intensity of ZnS:Cu nanopowders corresponds to sample with Cu concentration of 0.2%. To investigate the effect of polyvinylacohol (PVA) on the structure of ZnS:Cu, we have prepared the polyvinylacohol (PVA)-capped ZnS:Cu thin films with a Cu concentration of 0.2% by dip-coating method. The PVA did not affect the microstructure of ZnS nanomaterials. The optical properties of samples were studied by measuring the absorption and the photoluminescence spectra in the wavelength range from 300 nm to 900 nm at room temperature. The value of direct band gap is about 3.8 eV. The dependence of the photoluminescence (PL) spectra of samples on the exciting power density, their time-resolved-luminescence spectra were also investigated.